Archivist and Archives Management In Digital Era - Layla Rahmadanty; Veithzal Rivai Zainal; Azis Hakim (Greenation Research & Yayasan Global Resarch National, 2023)
In this digital era, everything is technology-based, so that Human Resources in carrying out their work must develop according to the speed of development. Archivists are Human Resources in the field of archives that are highly exposed to the development of digital technology. Previously Archive was always identified with the activity of managing old and dusty archives. Whereas Archivists in this era must be able to manage archives both conventionally and digitally or electronically. Archivists in this case must continually improve the quality and competency they possess, one of which is by increasing their capabilities in the field of records management. Archivists must change their way of thinking in managing archives, which were previously based on conventional to electronic based records management. Archivists must be able to adjust to technological developments so they can use computer systems in their work to manage records.